Verstedeliking: Riglyne vir 'n kerklike bediening - B. du T. Jackson (Acta Theologica, 2022)
With the process of accelerated urbanization it is important that the family of D.R. Churches should focus its ministry on the squatter communities. According to the Bible God in Christ never turned his back on the city, in spite of the concentration of sin within it, he is present with his children in the city. In all spheres of city life signs of God's Kingdom should be erected. Clear policy on urbanization was never found in S.A. and the socioeconomic powers dominated any political considerations. The normal process of urbanization did not always take place. The expectations for a better living was very often not realized with the resulting immense poverty. The church should plan for an urgent short and long term ministry for these communities. While the gospel is proclaimed, lost members should be located and those in need should urgently be cared for. The official ministry of the local congregation should be started together with the training of members to witness from within these communities. A functional building could be erected which could serve as a church and community center. In cooperation with other churches the extended christian witness should include diaconal services for the establishement of a stable community.